A STUDY ON ENGLISH GRAMMAR AND PRAGMATICS COMPETENCE OF INDONESIAN SPEAKERS - Ermansyah, Ermansyah (JOURNAL OF ADVANCED ENGLISH STUDIES, 2019)
The aim of the research were (1) to examine and explain the role of English Grammar Competence toward English Pragmatic competence, (2) to find evidence of the conjunction of pragmatic and Grammar competence of Indonesian English Speakers. Qualitative and quantitative methods were applied to analyze the result of the findings. English Grammar competence test (IELTS model test) was given to determine the subjects of the research Grammar competence. The English pragmatic test was given to determine the subject of the research competence on English pragmatic. The subjects of the research were grouped into 3 (three) categories; group A which consist of subjects whose English Grammar competence are at basic level (IELTS score 5 to 6), group B consists of subjects whose English Grammar competence are at intermediate level (IELTS score 6 – 7) and group C consists of subjects whose English Grammar competence are at Advance level (IELTS score above 7). Each group consists of 5 individuals, who have no prior information of the test model and the aims of the research. The English Grammar competence (IELTS model) is administered before the pragmatic competence test, to group the subjects of the research. The grouping can also be fulfilled by subjects’ official IELTS statement of result. There are 3 parts of the English Pragmatic Competence which researcher applied to determine the result of the research, (1) identifying formal, informal and neutral request utterances, (2) Expressing subjects willingness and unwillingness with reasons in using the utterances (3) Answering appropriately to multiple questions. The result of the research shows various result from the three levels examined of the English Grammar competence level. The research result also showed the strong conjunction between Grammar and pragmatic competence at higher level or at the third group where the students with higher competence at grammar has higher score on the pragmatics competence as well. The research result surprisingly shows low level of pragmatics competence at the second or those who has intermediate grammar competence and low levels of pragmatics competence to the first group, those who has basic Grammar competence